Zakat Distribution Research: A Bibliometric Analysis Using VOSViewer for the 2015–2024 Period - Farah Syadza Salsabila; Windi Windi (Journal of Waqf and Islamic Economic Philanthropy, 2025)
Economic inequality in Indonesia remains high, and personal poverty continues due to uneven income distribution. Zakat, as part of Islamic economic philanthropy, plays an important role in alleviating poverty by redistributing wealth. This study employs a bibliometric analysis using data from the Dimensions AI database, focusing on the keywords "Zakah and Distribution" in article titles. A total of 91 documents from 2015 to 2024 were analyzed using standard bibliometric indicators such as publication year, document type, source title, language, study field, keyword analysis, geographic distribution, authorship, institutions, and citation metrics. The findings highlight the significant influence of countries such as Indonesia and Malaysia in zakat research, with 2018 being the most prolific publication year. The VOSViewer tool was used for data visualization, revealing trends, co-authorship networks, citation clusters, and keyword co-occurrence.